Safety and efficacy of n-3 enriched nutritional supplements in the management of cancer cachexia - Klopper, Tanya (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--University of Stellenbosch, 2006.